2018
DOI: 10.3389/fneur.2018.00853
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Arm Rehabilitation in Chronic Stroke Patients With Aphasia May Promote Speech and Language Recovery (but Effect Is Not Enhanced by Supplementary tDCS)

Abstract: Objective: This study aimed to determine the extent to which robotic arm rehabilitation for chronic stroke may promote recovery of speech and language function in individuals with aphasia.Methods: We prospectively enrolled 17 individuals from a hemiparesis rehabilitation study pairing intensive robot assisted therapy with sham or active tDCS and evaluated their speech (N = 17) and language (N = 9) performance before and after a 12-week (36 session) treatment regimen. Performance changes were evaluated with pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To explore its clinical effect, some researchers used M1-tDCS to intervene in patients with PSA. The results show that M1-tDCS can improve aphasia patients' motor and communication function in conjunction with enhancing the retrieval ability of action-related words in the long term [ 16 ]. Interestingly, studies demonstrated that language function could be improved by asking patients to watch videos of task-oriented movements of the UE with voice guidance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore its clinical effect, some researchers used M1-tDCS to intervene in patients with PSA. The results show that M1-tDCS can improve aphasia patients' motor and communication function in conjunction with enhancing the retrieval ability of action-related words in the long term [ 16 ]. Interestingly, studies demonstrated that language function could be improved by asking patients to watch videos of task-oriented movements of the UE with voice guidance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, current studies rarely focus on simultaneous UE motor dysfunction with language deficits and even less on both functions' concurrent recovery during stroke recovery. Most studies only unexpectedly found this phenomenon or were mostly exploratory paradigm intervention studies [1,[14][15][16]. Few studies have focused on the difference in UE motor function status between patients with PSA and nonphasic poststroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Harnish et al, 58 following 6 weeks each of 2 exercise regimens, one using aerobic exercise and one involving stretching, both followed by speech therapy, those patients with aphasia receiving aerobic exercise demonstrated greater language gains. Even more recently, in a preliminary study of 17 patients with aphasia and rightsided hemiparesis, Buchwald et al 6 cautiously reported language gains following 36 sessions of robot-assisted arm treatment without the benefit of speech therapy, echoing the earlier study by Hesse et al 55 , while noting the need for further controlled experiments.…”
Section: Aphasia Research and Treatmentmentioning
confidence: 92%
“…One exciting perspective that is emerging from these multidisciplinary studies is the potential interaction between motor and aphasia recovery. 5,6 Increasingly, collateral effects on language production and comprehension have been reported as a result of the observation of movement. 7 Not coincidentally, given the close proximity of hand-arm and speech-language neural structures, in many patients with poststroke aphasia, the contralesional hand and arm are often simultaneously impaired.…”
Section: The Problemmentioning
confidence: 99%
“…The recovery process results can be improved by varying the force applied by the mechanical devices, increasing the movement amplitude, decreasing assistance, and increasing resistance, even with less supervision from therapists [ 2 ]. Aphasia, language rehabilitation, and shoulder-hand neuropathic pain may also benefit from robotic-assisted therapy [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%